History and Progress of Fractional-Order Element Passive Emulators: A Review - A. Kartci; N. Herencsar; J. T. Machado; L. Brancik (Radioengineering, 2020)
This paper presents a state-of-the-art survey in the area of fractional-order element passive emulators adopted in circuits and systems. An overview of the different approximations used to estimate the passive element values by means of rational functions is also discussed. A short comparison table highlights the significance of recent methodologies and their potential for further research. Moreover, the pros and cons in emulation of FOEs are analyzed.